ISLAMIC RELIGIOUS EDUCATION IN PLURAL SOCIETIES: ROLES, CHALLENGES, AND STRATEGIES FROM A SYSTEMATIC LITERATURE REVIEW - Saca Suhendi; Sarbini; Kiki Miftahul Hakiki; Taupik Hamdani; Hani Rolis (SOSIOEDUKASI, 2025)
Plurality is an unavoidable social reality in Indonesia's diverse society. Religious, cultural, and ethnic diversity pose unique challenges for the education system, especially Islamic Religious Education (IRE), which is responsible for shaping students' character and religious attitudes. This study aims to analyze the role, challenges, and strategies of Islamic Religious Education in dealing with plurality through a Systematic Literature Review (SLR) approach. Data were collected from 12 scientific articles indexed by Google Scholar published between 2020 and 2025. The results of the study show that PAI has a strategic role in instilling values of tolerance, religious moderation, and respect for differences. The main challenges faced include resistance to pluralism, a lack of teacher competence in multicultural learning, and a curriculum bias that is still normative. The strategies that emerged include strengthening multicultural education, curriculum innovation, developing teacher competencies, and synergy between educational institutions and the community. These findings confirm that the success of IRE amid plurality depends on the ability to adapt and integrate the values of Islam rahmatan lil 'alamin into inclusive and dialogical educational practices.